The Effects of Age, Control Beliefs, and Feedback on Self-Regulation of Reading and Problem Solving - Soederberg Miller, Lisa M.; West, Robin L. (Experimental aging research, 2010)
The authors examined the effects of adult age and control beliefs on self-regulatory responses to feedback using a false-feedback paradigm. Young and older adults read and attempted to solve a series of problems and periodically received either high- or low-performance feedback. Self-regulatory processes were assessed in terms of task-specific beliefs consisting of self-efficacy and performance expectations as well as degree of attention allocated to reading the mysteries. Results showed that high-performance feedback increased self-efficacy and performance expectations relative to low-performance feedback and that these effects were comparable across levels of preexisting control beliefs and across age groups. However, the effects of feedback on attention were moderated by age and preexisting control beliefs. Older adults in the high-performance feedback condition who had high levels of control beliefs allocated more attention to the text than did their low-control peers. These findings suggest that positive feedback may encourage older adults to engage more fully in a reading task, but only when they possess a strong sense of control.